2015
DOI: 10.1080/19443994.2014.943061
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration as post-treatment of MBR treating landfill leachate

Abstract: Landfill leachate management has been a major environmental, economic, and social concern, and its treatment brings forth a challenge, especially regarding the high concentration of refractory organic matter, ammonia, and toxic compounds, which may vary considerably depending on the maturity, age, and biochemical reactions occurring in the landfill, besides the high variation on the volume generated. This study was aimed to investigate NF use as a post-treatment of landfill leachate that has been treated by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Liu et al [160] performed an innovative combined treatment process of air stripping, Fenton, SBR and coagulation, finding high COD and NH 4 -N removal rates of 92.8% and 98%, respectively. Amaral et al [161] suggested a landfill treatment configuration consisting of an association of air stripping, MBR, and a NF (nano-filtration) membrane which has shown excellent performance, especially regarding the removal of COD (80%-96%), ammonia (85%-95%), color (98%-99.9%), and phosphorus (78%-99.8%). Gao et al [162] introduced an integrated approach with the continuous recirculation of ozonated autotrophic nitrogen removal (ANR) effluent, showing the possibility to reach a COD removal as high as 40% in the ANR with a slight decrease in nitrogen removal of around 70%-80% when compared with no leachate ozonated recirculation.…”
Section: Combination Of Physical-chemical and Biological Processesmentioning
confidence: 99%
“…Liu et al [160] performed an innovative combined treatment process of air stripping, Fenton, SBR and coagulation, finding high COD and NH 4 -N removal rates of 92.8% and 98%, respectively. Amaral et al [161] suggested a landfill treatment configuration consisting of an association of air stripping, MBR, and a NF (nano-filtration) membrane which has shown excellent performance, especially regarding the removal of COD (80%-96%), ammonia (85%-95%), color (98%-99.9%), and phosphorus (78%-99.8%). Gao et al [162] introduced an integrated approach with the continuous recirculation of ozonated autotrophic nitrogen removal (ANR) effluent, showing the possibility to reach a COD removal as high as 40% in the ANR with a slight decrease in nitrogen removal of around 70%-80% when compared with no leachate ozonated recirculation.…”
Section: Combination Of Physical-chemical and Biological Processesmentioning
confidence: 99%
“…For example, a study on ultrafiltration of biologically treated leachates showed an increase of UV absorbance removal close to 43% when pore size decreased from 700 nm to 7 nm; in this pore size range, HA and FA were mainly retained; for pore size of 4 nm, additional UV absorbance removal was obtained due to retention of HPI [60,61]; in consequence, the smaller the pore size, the greater the removal of UVQS. The main handicap of using membranes to remove UVQS is the increase of membrane fouling in the presence of these compounds [62,63].…”
Section: Physical Treatmentsmentioning
confidence: 99%
“…The obtained results presented high COD (92.8%) and NH 4 + ‐N (98%) removal rates. Amaral and his co‐workers [ 25 ] performed an LFL treatment method consisting in air stripping associated with a membrane bioreactor using a nanofiltration membrane. This system has shown good performances for the removal of COD, ammonia, color, and phosphorus, where the recorded values exceeded 80%.…”
Section: Introductionmentioning
confidence: 99%